Effectiveness of a training program in compliance with recommendations for venous lines care. Issue 1 (December 2015) - Pérez-Granda, M.; Guembe, M.; Rincón, C.; Muñoz, P.; Bouza, E.
Abstract Background The impact of training programs on the care and maintenance of venous lines (VL) has been assessed mainly in patients admitted to the intensive care unit (ICU). Data on the impact of such programs in a whole general hospital are scarce. The objective of this study was to assess compliance with VL care after an extensive training program aimed at nurses caring for adult ICU and non-ICU patients. Methods We performed 2 point prevalence studies in a general hospital. A specialized nurse visited all hospitalized adult patients, performed a bedside inspection, and reviewed the nursing records for patients with a VL before and after a 1-year training program. The program included an interactive on-line teaching component and distribution of pocket leaflets and posters with recommendations on VL care. Results Data recorded for the first and second prevalence studies were as follows: number of patients visited, 753 vs. 682; total number of patients with ≥ 1 VL implanted on the visit day, 653 (86.7 %) vs 585 (85.8 %); catheters considered unnecessary on the study day, 183 (22.9 %) vs 48 (7.1 %) (p  < 0.001); number of catheters with local clinical evidence of infection on the study day, 18 (2.2 %) vs 12 (1.8 %) (p  = 0.52); registration of insertion day (42.3 % vs 50.1 %;p  = 0.003); and registration of day of dressing change (41.2 % vs 49.1 %;p  = 0.003). Maintenance parameters improved more in non-ICU than in ICU patients. Conclusion A multidisciplinary teaching program to improve VL care and compliance with recommendations is effective. Point prevalence studies are easy to carry out and effective at demonstrating increases in compliance, mainly in non-ICU patients.